REHABILITASI POST NERVE TRANSFER PADA EKSTREMITAS ATAS - Satria Nugraha, Made Hendra (Jurnal Vokasi Indonesia, 2021)
Peripheral nerve injuries mostly occur in the upper extremities with the most common cause being trauma. An alternative to nerve repair in proximal injury is restoration of function via nerve transfer. The rehabilitation process is needed to relearn the movement so that the results of the nerve transfer can function properly. The purpose of this study was to provide an overview of the post-nerve transfer rehabilitation process in the upper extremity and its benefits in maintaining and improving the quality of movement in the upper extremity. This research is a literature review with secondary data sources in the form of scientific journals accessed through journal databases, such as: PubMed Central (PMC) NCBI and google scholar. Based on the study conducted, it is recommended that three stages in rehabilitation after nerve transfer in the upper extremities are recommended, namely: 1. Early phase: immobilization and education procedures are carried out for patients related to the surgical procedure and the rehabilitation stages to be followed, 2. Middle phase: conducting a re-innervation of neural pathways and motor re- learning with various modalities or approaches, such as: induction exercise, cross over training, graded motor imagery, electrical stimulation, surface electromyography, and aquatic therapy, 3. Late phase: all exercise in the middle phase is continuing and added with an approach in the form of muscle strength and endurance training that takes attention to the biomechanical aspect. Post nerve transfer rehabilitation is useful in maintaining and improving the quality of upper extremity movement and it is recommended that its application be adjusted to the rehabilitation phase.